Role of germinal center and CD39ʰⁱᵍʰCD73⁺ B cells in the age-related tonsillar involution - Pastor, Rocío (2024)
Background The tonsils operate as a protection ring of mucosa at the gates of the upper aero-digestive tract. They show similarities with lymph nodes and participate as inductive organs of systemic and mucosal immunity. Based on the reduction of their size since puberty, they are thought to experience involution in adulthood. In this context, we have used tonsillar mononuclear cells (TMC) isolated from patients at different stages of life, to study the effect of ageing and the concomitant persistent inflammation on these immune cells. Results We found an age-dependent reduction in the proportion of germinal center B cell population (BGC) and its T cell counterpart (T follicular helper germinal center cells, TfhGC). Also, we demonstrated an increment in the percentage of local memory B cells and mantle zone T follicular helper cells (mTfh). Furthermore, younger tonsils rendered higher proportion of proliferative immune cells within the freshly isolated TMC fraction than those from older ones. We demonstrated the accumulation of a B cell subset (CD20⁺CD39ʰⁱᵍʰCD73⁺ cells) metabolically adapted to catabolize adenosine triphosphate (ATP) as patients get older. To finish, tonsillar B cells from patients at different ages did not show differences in their proliferative response to stimulation ex vivo, in bulk TMC cultures. Conclusions This paper sheds light on the changing aspects of the immune cellular landscape, over the course of time and constant exposure, at the entrance of the respiratory and digestive systems. Our findings support the notion that there is a re-modelling of the immune functionality of the excised tonsils over time. They are indicative of a transition from an effector type of immune response, typically oriented to reduce pathogen burden early in life, to the development of an immunosuppressive microenvironment at later stages, when tissue damage control gets critical provided the time passed under immune attack. Noteworthy, when isolated from such histologic microenvironment, older tonsillar B cells seem to level their proliferation capacity with the younger ones. Understanding these features will not only contribute to comprehend the differences in susceptibility to pathogens among children and adults but would also impact on vaccine developments intended to target these relevant mucosal sites.